Statistical Approach to Students’ Psychological Conflicts Towards Primary to Higher EducationBy Using Big Data - Thilakavalli, Mrs.K. (International Journal of Basic and Applied Sciences, 2025)
Curriculum refers to all the educational activities of the school, and it is broader. Teachers are changing the behaviour of students in terms of growth in career and knowledge. Conflict-inducing attitudes of teachers and students have a negative impact, and they can hamper students’ learning processes. Effective conﬂict management not only reduces disruption to the learning process but also supports the development of students’ social and emotional skills, such as problem solving, empathy, and communication. To initiate a process of conceptual change, the students must be motivated and interested in the topic, activate their prior knowledge, and have certain epistemological beliefs and reasoning abilities adequate to deal with the given problem. The objective of the paper is to identify the students’ psychological conflict in the curriculum who promotes school education to higher education. Therefore, to gain the objective, the data was collected from the 240 students by using a cloud-based Linux Operating System supporting a questionnaire application. Out of 240 Students, 180 students’ data were chosen by using Likert scaling and interviewing method. Descriptive Statistics and Percentage Analysis have been implemented for analysis. Finally, it was concluded that Administrators of the Institutions and teachers must concentrate to create positive thought towards selection of Course, Curriculum, learning infrastructure, Technological implementation in classroom, Future career by using welcoming, orientation, skilled teacher’s lectures, training programmes, enriched laboratory facilities and it should be reduced stigma around mental health. In addition, teachers must concentrate on creating the course plan for their handling courses before starting the class, and the management should concentrate on creating positive thoughts about the course through the Welcoming booklet.